PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA MELALUI MEDIA FLASHCARD PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV DI SDN 4 LIMBOTO BARAT - Riska R. Utina; Harni Jusuf; Sitti Rahmawati Talango (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine the application of flashcard media in improving students' reading comprehension skills in Indonesian language subjects in grade IV of SDN 4 Limboto Barat. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles. The research subjects are 20 students, consisting of 8 male students and 12 female students. Based on the results of the study after applying flashcard media, where student learning outcomes in cycle I meeting 1, 9 students (45%) completed and 11 students (55%) did not complete, then continued to cycle 1 meeting II where 11 students (55%) completed and 9 students (45%) did not complete. Because it has not achieved learning outcomes in accordance with the provisions, the researcher continued to Cycle II where in cycle II meeting 1, 14 students (70%) completed and 6 students (30%) did not complete. Then continued again in cycle II stage II where in cycle II meeting II, 18 students (90%) completed and 2 students (10%) did not complete. Thus, the application of flashcard media in learning Indonesian language material on short stories can improve the reading comprehension skills of fourth grade students at SDN 4 Limboto Barat.